Pendampingan Pengembangan Nilai Budaya Daerah Melalui Konten Web Series - Sugiarto, Claudia; Aditya Sanjaya, I Dewa Gede; Hydanta, Jan Asher; Kurniasari, Jessica Gabrielle; Fernando, Kevin; Sendana, Ravella; Raharjo, Ricardo Anthony; Cahyadi, William Anthony (Pusat Pengabdian kepada Masyarakat (PPKM) Universitas Prasetiya Mulya, 2022)
Community Development (COMDEV) activities at Prasetiya Mulya University are carried out with the aim of developing businesses and products produced by partners in collaboration with the University. Partners who collaborate with the University are majoring in film from Banjarmasin Vocational School. The challenge that is owned by SMK Banjarmasin is how to find the right target market but does not eliminate the strong Banjar regional culture. Films produced by partners so far have only been published in film festival competitions, so they are less profitable. Based on the situation analysis conducted by the group, several improvements have been made in terms of operations, marketing, human resources and finance. These improvement steps were realized with the existence of new social media and also the creation of a web series that was broadcast on Youtube with the concept of